Histopathological Effect Of Artesunate In Chicks Liver Subjected To Exposure To Artesunate At Embryonic Stage. - Kumar Ray, Sudhakar; James, Jessie; Kumar Ashoka, Ram; Meraj Alam Fatmi, Syed; Sangeeta, Sangeeta (Journal of Neonatal Surgery, 2025)
Introduction: Artesunate is obtained from the Artemisia plant, scientifically referred to as Qinghaosu, and is indigenous to China. Artemisinin derivatives are a specific group of drugs that have the highest effectiveness in treating Chloroquine resistant Plasmodium vivax and Plasmodium falciparum malaria compared to all other antimalarial drugs available. Malaria imposes a substantial socio-economic burden on the population of India, experiences approximately two million cases of malaria each year, leading to a substantial number of deaths. The chick embryo is commonly used as an animal model to investigate the harmful effects of various drugs in research. The objective of this study is to assess the histopathological effects of artesunate on the liver of developing chick embryos. Material & Methods: A total of 165 eggs of Gallus domesticus were used for this study. On the 5th day, eggs were injected with artesunate and normal saline as per dose titration, divided into four experimental groups and control groups. Further incubation and manual hatching were done on 18th day. Liver was isolated from the embryo for histological slide preparation; further analysis of each slide was done under a binocular microscope to determine the histopathological changes and abnormalities. Results: Based on histopathological analysis, we observed the abnormalities of fat deposition and fatty changes, sinusoids with mild to severe lymphocyte infiltration, sinusoidal dilation, sinusoidal congestion, extensive inflammatory changes, and liver degeneration. Conclusion: The recommended dose of artesunate has a mild hepatotoxic effect but teratogenic risk increases with an increase in drug dose in the liver.